Riboswitch-controlled IL-12 gene therapy reduces hepatocellular cancer in mice - Düchs, Matthias J.; Kratzer, Ramona F.; Vieyra-Garcia, Pablo; Strobel, Benjamin; Schönberger, Tanja; Groß, Peter; Aljayyoussi, Ghaith; Gupta, Aradhana; Lang, Isabel; Klein, Holger; Morilla, Sandra Martinez; Hopf, Stefan; et al. (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) and solid cancers with liver metastases are indications with high unmet medical need. Interleukin-12 (IL-12) is a proinflammatory cytokine with substantial anti-tumor properties, but its therapeutic potential has not been realized due to severe toxicity. Here, we show that orthotopic liver tumors in mice can be treated by targeting hepatocytes via systemic delivery of adenoassociated virus (AAV) vectors carrying the murine IL-12 gene. Controlled cytokine production was achieved in vivo by using the tetracycline-inducible K19 riboswitch. AAV-mediated expression of IL-12 led to STAT4 phosphorylation, interferon- (IFN) production, infiltration of T cells and, ultimately, tumor regression. By detailed analyses of efficacy and tolerability in healthy and tumor-bearing animals, we could define a safe and efficacious vector dose. As a potential clinical candidate, we characterized vectors carrying the human IL-12 (huIL-12) gene. In mice, bioactive human IL-12 was expressed in a vector dose-dependent manner and could be induced by tetracycline, suggesting tissuespecific AAV vectors with riboswitch-controlled expression of highly potent proinflammatory cytokines as an attractive approach for vector-based cancer immunotherapy.